2004
DOI: 10.1016/j.virol.2004.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in Sindbis virions resulting from exposure to low pH and interactions with cells suggest that cell penetration may occur at the cell surface in the absence of membrane fusion

Abstract: Alphaviruses have the ability to induce cell-cell fusion after exposure to acid pH. This observation has served as an article of proof that these membrane-containing viruses infect cells by fusion of the virus membrane with a host cell membrane upon exposure to acid pH after incorporation into a cell endosome. We have investigated the requirements for the induction of virus-mediated, low pH-induced cell-cell fusion and cell-virus fusion. We have correlated the pH requirements for this process to structural cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
115
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 56 publications
5
115
2
Order By: Relevance
“…The authors of this paper (43) suggested that classical membrane fusion did not occur but that entry was similar to that seen for poliovirus (19), which has no membrane. The E1 and E2 protein icosahedron cover the alphavirus membrane so it unavailable for contact with the host cell membrane, but changes of the E1 and E2 proteins after binding of the virion may solve that problem.…”
Section: Membrane Uncoating Of Other Virusesmentioning
confidence: 68%
See 3 more Smart Citations
“…The authors of this paper (43) suggested that classical membrane fusion did not occur but that entry was similar to that seen for poliovirus (19), which has no membrane. The E1 and E2 protein icosahedron cover the alphavirus membrane so it unavailable for contact with the host cell membrane, but changes of the E1 and E2 proteins after binding of the virion may solve that problem.…”
Section: Membrane Uncoating Of Other Virusesmentioning
confidence: 68%
“…In a paper that addressed mainly the effects of pH changes on virus structure, a final section showed transmission electron micrographs of Sindbis viral entry at neutral pH (43). Sindbis virus strain SVHR produces virus with a low particle/ PFU ratio, usually between 1 and 10 (18).…”
Section: Membrane Uncoating Of Other Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of these viruses at pH values ∼5.0−5.9 have been examined using cryoelectron microscopy (cryo-EM) and 3D reconstruction techniques (22)(23)(24)(25); however, low-pH-triggered conformational rearrangements of the virus in the context of a target membrane are rarely investigated via these techniques (26). Here we present a cryo-EM study of SINV TE12 in complex with a liposomal membrane at pH 6.4.…”
mentioning
confidence: 99%